Effect of whey protein derivatives on cell viability, cell migration and cell cycle phases in MCF-7 cells - YILMAZ GÖLER, AYŞE MİNE; YALÇIN, AHMET SUHA (My University, 2023)
Objective: This study aimed to obtain protein derivatives after treatment of whey proteins with hazelnut oil and olive oil and determined their effects on MCF-7 cells. Materials and Methods: Whey proteins obtained from 6% whey powder were treated with hazelnut oil (HO) and olive oil (OO) at a protein to lipid ratio of 1:10 at 60 ̊C for 120 minutes. The protein derivatives formed with whey protein and HO or OO were applied to MCF-7 cancer cells and healthy fibroblasts. The effects of protein derivatives on cell viability, apoptosis, reactive oxygen species (ROS) production, wound healing, cell cycle phase distribution and cell cycle related proteins Akt and p21(Waf1/Cip1) expressions were investigated. Results: Cell viability decreased significantly after 24 h of incubation with WP:OO. The percentage of apoptotic or necrotic cells varied between 5-10% and no statistically significant effect was observed. There was no statistically significant difference in ROS production and colony formation between controls and WP:HO or WP:OO groups. Treatment of cells with WP:OO for 24 h significantly decreased cell migration compared to the control group. G2/M phase was significantly suppressed in WP:OO group compared to the control group. WP:OO also increased the expression of p21(Waf1/Cip1) significantly when compared with the control group. Conclusion: Our results showed that whey protein derivatives applied to MCF-7 cells are cytotoxic and may be useful in breast cancer treatment
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Whey proteins; Oleic acid; Cell survival; Apoptosis; Cell cycle; HUMAN ALPHA-LACTALBUMIN; OLEIC-ACID; OLIVE OIL; CYTOTOXIC COMPLEXES; TUMOR-CELLS; HAMLET; CANCER; BOVINE; LETHAL; APOPTOSIS; Whey proteins; Oleic acid; Cell survival; Apoptosis; Cell cycle